THE STUDY OF RISK FACTOR AND STRATEGIES FOR PREVENTION OF RECURRENT ISCHEMIC STROKE :A COMPREHENSIVE SYSTEMATIC REVIEW - Ibni Rizal, Ibnu; Octaviantie, Ghiffany (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Studies show that the majority of strokes are caused by modifiable risk factors, such as high-fat diets, sleep apnea, diabetes, heart disorders, and other diseases. Recurrence rates are higher in sub-Saharan Africa (SSA), where strokes occur in the fourth or fifth decades of life. To reduce the risk of stroke recurrence and death, individuals who have survived their first stroke must undergo regular medical follow-up. Understanding the risk factors for stroke recurrence can help create plans and treatments to lessen the burden of strokes. Regular medical follow-up and understanding these risk factors can help create effective treatments and plans to reduce stroke recurrence. Methods: This systematic review focused on full-text English literature published between 2014 and 2024, adhering to PRISMA 2020 principles. Without a DOI, editorials and review papers that were published in the same journal as the submission were not accepted. ScienceDirect, PubMed, and SagePub were among the many web resources used to compile the literature. Result: Using reliable resources including Science Direct, SagePub, and PubMed, the study examined over 7,000 publications. Following the determination that seven publications warranted a further inquiry, a more thorough examination of the full corpus was conducted. Conclusion: Risk factors such as hypertension, alcohol consumption, diabetes, female gender, non-adherence to treatment, and cardiac causes contribute to high stroke recurrence rates in sub-Saharan Africa. Treatment effectiveness varies among ethnic groups, with DAPT being effective in patients with ICAD. Statin-based therapies reduce recurrent stroke risk but increase hemorrhagic stroke risk. Vitamin D plays a crucial role in brain development.